Primitive Neuroectodermal Tumour (PNET) With Divergent Differentiation In Frontal Lobe - Khan, Muhammad Ihtesham; Khalid, Ahmareen (International Journal of Pathology, 2018)
Primitive neuroectodermal tumors (PNETs) of brain are childhood tumours which are frequently located in cerebellum.Supratentorial PNETs are uncommon. These tumors are composed of undifferentiated or poorly differentiatedcells of neuroectodermal origin, with the capacity for differentiation along neuronal, astrocytic, ependymal,and melanocytic cell lines. PNET with divergent differentiation in frontal lobe of brain is a rare phenomenon. Acase of 6 years old female child having PNET with divergent differentiation (ependymal and neuroblastomal differentiation)in frontal lobe of brain is reported